MONTHLY VARIATIONS OF THE EPIPELIC AGAL COMMUNITIESIN AL-AaRAS TOURIST ISLAND LAKE , BAGHDAD - IRAQ - Al-Tamimi, Abdul-Nasir (Iraqi Journal of Science, 2024)
Three sites at the Al-aaras tourist island lake were selected to study the physicochemicalcharacters and epipelic algal communities . Monthly samples for 12 monthwere taken starting January 2009 . It was found that the lake is alkaline , welloxygenated ,oligohaline with low electrical conductivity and hard water . Theconcentration of reactive nitrite ( NO3) were available and low concentration ofreactive phosphate ( PO 4 ) . A total of 67 taxa were identified dominated byBacillariophyceae ( 65.7 % ) followed by Cyanophyceae ( 16.4 % ) andChlorophyceae ( 13.4 % ) . Clear seasonal variations in the total density of epipelicalgae were found at different studied sites with a binomial pattern at spring andautumn . The total cell number was ranged between 0.09 x 10 4 – 14.0 x 10 4 Cell/ cm² . Almost similar binomial peaks also found in Bacillariophyceae , out of 11taxa identified of Cyanophyceae , 6 were belong to Oscillatoria . WhileScenedesmus quadricauda was composed of high cell number of Chlorophyceae .